PERBANDINGAN PENDEKATAN TEORI NORMATIF DAN POSITIF DALAM KEBIJAKAN AKUNTANSI PADA PT ASTRA INTERNATIONAL TBK (MANUFAKTUR) DAN PT TELEKOMUNIKASI INDONESIA TBK (TEKNOLOGI) DI INDONESIA - Amalya Ahmad, Dwi Rezky; Nawangsari, Ajeng Tita (Universitas Muhammadiyah Gorontalo, 2025)
This study examines how theoretical orientations in accounting policy manifest within two leading Indonesian firms operating in distinct industrial sectors—manufacturing and technology—over the period 2017 to 2024. Employing a qualitative content analysis of corporate disclosures and relevant academic literature, the research investigates organizational responses to environmental pressures, governance mechanisms, and institutional expectations as reflected in financial reporting choices. The findings reveal contrasting strategic orientations: the manufacturing firm adopts conservative and rigid policies aimed at preserving legitimacy, while the technology firm pursues adaptive and flexible approaches aligned with innovation dynamics. These patterns reflect deeper institutional logics shaped by legitimacy concerns, agency relationships, and sector-specific value creation imperatives. The study concludes that accounting policy is best understood as a negotiated construct situated between normative ideals and pragmatic demands, highlighting the importance of theoretical pluralism in contemporary accounting practice